Effects of technique asymmetry on 500 m speed skating performance - Liu, Z.; Ding, M.; Zhang, M.; Yu, B.; Liu, H. (Bioengineering, 2024)
This study aimed to determine the effects of technique asymmetry on 500 m straight-track speed skating performance. We analyzed 20 elite skaters, measuring their joint angles, center of mass shift, and times and speeds during the gliding and push-off phases. The technique asymmetry index (ASI) was calculated for each parameter, and paired t-tests were used to compare bilateral asymmetry. Spearman correlation coefficients assessed the relationship between the ASI and both the average straight track speed and overall performance. Significant bilateral asymmetries in the knee, push-off, trunk, and hip angles were found in both male and female participants (p < 0.05). The male participants demonstrated a higher right push-off speed (p = 0.029) and a longer left gliding time (p = 0.048). Significant asymmetry was also observed in the lateral shift of the center of mass during each phase of the straight-track skating gait cycle (p < 0.001). No significant correlation was found between the ASIs and the overall performance (p = 0.067). These findings indicate that while elite speed skaters demonstrated significant bilateral technique asymmetry in straight track skating, these asymmetries did not significantly impact their overall performance.